Cross‐reactivity between decellularized porcine corneal lamellae for corneal xenobridging and subsequent corneal allotransplants. (11th December 2013) - Choi, Hyuk Jin; Lee, Jong Joo; Kim, Mee Kum; Lee, Hyun Ju; Ko, Ah Young; Kang, Hee Jung; Park, Chung‐Gyu; Wee, Won Ryang
Abstract The purpose of this study is to investigate cross‐reactivity between hypertonic saline‐treated decellularized porcine corneal lamellae for corneal xenobridging and subsequent corneal allotransplants. Five Chinese rhesus macaques, which had undergone anterior partial thickness corneal transplantation using hypertonic saline‐treated decellularized porcine corneal lamellae in preceding experiments, were used as recipients for subsequent full‐thickness corneal allografts. To determine whether sensitization of recipients to xenoantigens leads to cross‐reactivity against alloantigens, we compared; (i) allogeneic one‐way mixed lymphocyte reaction (MLR) of peripheral blood mononuclear cells (PBMCs) from xeno‐sensitized recipients with that of PBMCs from naïve rhesus macaques, and (ii) amounts of IgG antibodies that bound to the PBMCs of a rhesus panel (five monkeys) before and after xeno‐sensitization. Graft survival and immunologic profiles including memory T‐cell subsets and donor rhesus‐specific antibodies were also evaluated. No hyperacute or acute rejection was observed within a month of subsequent allotransplantation in any recipient. Alloreactivity by MLR was not different between xeno‐sensitized rhesus recipients and naïve rhesus monkeys. Panel‐reactive IgG antibodies were unchanged after xeno‐sensitization, and no change in donor rhesus‐specific antibodies was observed in any recipient. No significant changes in memory T‐cell subsets were observed during the early post‐operative period in any recipient. Decellularized porcine corneal lamellae may not increase cross‐reactivity to alloantigens, and thus, porcine corneal lamellae may be used as a bridge to subsequent corneal allografting.